STUDY RECOMMENDATIONS TO ACHIEVE THERMAL COMFORT IN AN EDUCATIONAL BUILDING - Naufal Andi Irsyad; Kartika Rahmasari; Ova Candra Dewi (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2023)
This paper evaluates natural ventilation effectiveness in one fully dependent Air Conditioned-Educational Building in Depok to recommend potential passive cooling approaches toward user thermal comfort. This study involves building surveys to measure the temperature and humidity of three selected classrooms, A, B, and C, with varying configurations and capacities. Airflow simulation using Computational Fluid Dynamics (CFD) is done under two conditions: open and closed doors. A set of parameters, which are room configuration, type of window, and ventilation strategy, are set to evaluate natural ventilation aspects. The site survey indicates that only one classroom with an area of 92 sqm facing to the southside is classified as efficiently warm (Room A). The simulation demonstrates that cross-ventilation only occurs when the door is opened. The parameters indicating shape, dimension, type, and area of natural ventilation matter, show that the building’s natural ventilation is ineffective in providing thermal comfort. This study recommends that the building’s natural ventilation be placed according to the direction of the airflow, adding vertical fin elements, and increasing the openings by more than 5% area from the floor area.